An Overview of the East-Asian Economic Crisis - Yong, Chee Leong (1998)
The objective of this project is to analyse the possible causes and the effects of the economic crisis in East-asian region with particular emphasis of the impact on Malaysia in respect of the RINGGIT and the KUALA LUMPUR STOCK EXCHANGE; how the crisis affects countries in other regions. The issues of whether the I MF can solve the prevailing problems in this region and how Mexican's crisis is different from the East-asian are also discussed. Lastly, several recommendations are made with a view to strengthen and improve the economic fundamentals of Malaysia. The possible causes of the crisis incudes: poor financial and banking system resulting in substantial non-performing loans, Investors' loss of confidence, less competitive exports, unproductive investments and over-dependence on the foreign capital. Malaysia was hit badly by this crisis. The value of Ringgit fell from 2. 6450 in July 1997 to 4. 1 550 against the US Dollar in July 1998 whilst the Composite Index fell from 1,0 1 2. 84 in July 1997 to 402.65 in July 1998 . The Gross Domestic Product ( GDP ) growth rate was forecasted to be - 1% to -2% compared with the average GDP growth rate of 8.8 % for the period between 1988 to 1997.It is evident that IMF cannot provide solution to East-asian countries as countries who resorted to I MF's bail-out do not seem to recover from their crisis. East-asian's crisis is by nature different from that of the Mexican's crisis in 1995. The former is solvency crisis whereas the latter is liquidity crisis. Malaysian government should strengthen its economic fundamentals by implementing several measures such as making it compulsory to make use of local manufactured parts. Agriculture sector should be revived as it can save the country for RM 9 billion on food. To develop Information Technology, Education and Tourism sectors to generate foreign exchange for the country. Regulations should be imposed to prevent sudden outflow of foreign portfoliofunds. The Banking sectors has to be strengthen and not to allow politicians to have hands in the Banking industry loans should only be approved based on its merit only.